S113 Long Term Exercise (LTE) For COPD Patients Post-Pulmonary Rehabilitation (PR) Prolongs the Duration of Benefits Derived from PR. (19th November 2012) - Roberts, SE; Rogers, S; Segal, A; Purcell, S; Broomfield, H; Fabris, G; Calonge-Contreras, M; Billet, J; Restrick, L; Stern, M
Abstract : Introduction: PR is associated with functional, emotional and resource benefits for breathless COPD patients which decline over 12–18 months. Patients who complete PR express the desire to continue exercising regularly with other breathless patients but there is currently no evidence for efficacy. This study evaluated regular community-based LTEfor these patients. Methods: Patients completing PR were recruited to once weekly LTE held in accessible venues by 2 exercise instructors (Loughborough trained for exercising patients with chronic respiratory disease). Baseline demographics and disease severity were collected and outcomes: 6 minute walk test (6MWT), Hospital Anxiety & Depression (HAD) score, COPD Assessment Test (CAT), Chronic Respiratory Questionnaire (CRQ) and patient satisfaction measured at baseline, 6 and 12 months. Patients who accepted referral for LTE but never attended or dropped-out were recalled for outcomes at 12 months. Hospital admissions were audited for 12 months after PR-completion. Results: Between June-2010 and January-2012 75 patients mean(SD) age 69.3(9.7)yrs, FEV1 1.26(0.54)L, MRC 3.16(0.81) 63% female, 19.2% current smokers and 3 on LTOT accepted referral to LTE. 35% (26/75) never attended and 27%(20/75) dropped out after starting; 39% (29/75) continued to exercise for at least 6 months and 25% (19/75) exercised to 1 yr. For patients who exercised for 12 months there was no significant decline in exercise capacity (6MWT), a significant improvement in CAT over 6/12 (p=0.002) maintained to 12/12 (p=0.02) and no increase in anxiety levels, which remained below clinical relevance for the 12 months post PR. In comparison, patients who did not continue LTE had a significant (p=0.001) decline in 6MWT, no change in CAT score and a significant(p=0.04) increase in anxiety to a clinically important range (table 1 ). Self reported hospital admissions in the year following PR were higher for patients who did not exercise (mean 0.61 (SD 1.47)) compared to those who did, 0.16 (0.50). Conclusions: This pilot demonstrates that community-based LTE with trained instructors is safe and realistic for breathless patients after completing PR and, for the first time, demonstrates significant prolongation of functional and emotional benefits. This offers acheaper, more durable alternative to repeating PR.